Williamson and Coase - Libecap, Gary D. (National Bureau of Economic Research, 2024)
The governance and transaction cost insights of Oliver Williamson (1975, 1985, 1996, 2010) and Ronald Coase (1937, 1992) have framed antitrust polices and firm management strategies. Transaction cost economics explain efficient governance adaptation. With a focus on private efficiency gains within firms and markets, however, neither Williamson nor Coase explore political exchange and rent-seeking. Coase (1960) sought to reform Pigouvian externality regulation based on transaction cost efficiencies. He called for assignment of property rights and bargaining, and for institutional comparisons of costs and benefits to reveal relative transaction cost and welfare advantages. His 1960 paper is among the most cited in economics, but his remedies have not been adopted as the primary approach in major US environmental policies. All US environmental and natural resource laws since 1970 are Pigouvian. Limited Coasean bargaining occurs late and around the edges of the laws. The efficiency advantages, welfare gains, and collaborative responses Coase suggested have not been achieved. The Magnuson-Stevens Fishery Act of 1976, enacted 16 years after Coase, used Pigouvian fishery regulation for 25 years, and upon failure, was replaced by abbreviated property rights and trade. Fishery economic values were lowered relative to what might have been possible. The Endangered Species Act of 1973 rejected previous Coasean legislation authorizing purchase of critical habitat and instead opted for uncompensated Pigouvian controls on private landowners, who held most endangered species. Landowners resisted, and only 3% of listed endangered species have recovered. There is no evidence of a weighing of comparative transaction costs between Coase or Pigou in enacting any legislation. Rent-seeking via political bargaining among interest groups, politicians, and agency officials explains many of the observed patterns in externality regulation. The analysis suggests that transaction cost economics play a lesser role in the political arena
Hardcopy version available to institutional subscribers
Keywords: Arbeitspapier; Graue Literatur; Coase; R. H.; Williamson; Oliver E.; Transaktionskosten; Rent-Seeking; Internalisierung externer Effekte; Umweltpolitik; Umweltrecht; Ökonomische Ideengeschichte; Neue Institutionenökonomik; Property Law; Energy; Environmental; Health; and Safety Law; Agriculture; Natural Resources; Environment; and Extractive Industries; U.S.; Canada: 1913-; Pollution Control Adoption and Costs; Distributional Effects; Employment Effects; Air Pollution; Water Pollution; Noise; Hazardous Waste; Solid Waste; Recycling; Ecological Economics: Ecosystem Services; Biodiversity Conservation; Bioeconomics; Industrial Ecology; Government Policy